POLIGAMI: DARI FIQH HINGGA PERUNDANG-UNDANGAN - Atik Wartini (Hunafa: Jurnal Studia Islamika, 2013)
Abstract. Studies on polygamy is never finished, there's always pro and contra, in this study, the study of polygamy is focused on the study of law, fiqh study, and the study of hadith, and the view of some contemporary scholars on the issue of polygamy. Although just a description of the polygamy of the various rules, at the point of importance is the author's attitude towards the phenomenon of polygamy in Indonesia. Normative law that gives firmness in social life becomes important in this study. Normative approach is very thick in this paper, because the data used is based on a normative study. Regardless of the normative approach in this study to be one consideration in completing pro and contra on polygamy issues.Kata Kunci: Poligami, Hukum Islam, sarjana hukum Islam.